Age and Gender Wise Prevalence of Oral Habits - A Retrospective Study - Fahmida Binti Abd Rahman1 , Mahesh2 , T.N.Uma Maheshwari3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Oral habits are learned patterns of muscle contraction and have very complex nature. Persistent oral habitsbeyonds normal age of children have been considered as a significant factor that can lead to malocclusions.A total of 86000 case records between June 2019 to march 2020 were screened and evaluated in which18656 children less than 18 years were taken into our study. Chi square test was done to estimate therelationship between oral habits with age and gender. The results showed that the overall prevalence of oralhabits among children were 3.9%. The highest prevalence rate of oral habits was tongue thrusting (43.5%)followed by thumb sucking (39.1%) and lip biting (17.4%) respectively. Chi square test was done in betweenage and type of oral habits and the p value was 0.025< 0.05 was termed to be statistically significant. Withinthe limit of our study, oral habits were detected in less than quarter of the examined population. There was asignificant difference for age wise prevalence of oral habits, with younger people indulging more oral habitsthan elders. Among the types of oral habits, tongue thrusting was the commonest oral habits indulged amongthe children.